Paper-based devices as new smart analytical tools for sustainable detection of environmental pollutants. (December 2021) - Colozza, Noemi; Caratelli, Veronica; Moscone, Danila; Arduini, Fabiana
Abstract: The use of paper as a multifunctional material in electrochemical sensing has been intensively explored over the last decade. The combination among different kinds of paper as well as their coupling with different electrochemical cell configurations have been demonstrated, disclosing innovative sensing performances and features that are still to be fully investigated. This ongoing research has found applications in a variety of fields, including the biomedical, agri-food, security, and environmental ones, thanks to the high versatility and adaptability of the paper material. In this review, we report a critical and comparative analysis of electrochemical devices based on paper published within 2010–2021 and applied for the detection of pollutants of environmental interest in fresh water, seawater, and other real environmental matrices. Several paper types, from common office paper to Whatman filter paper with different filtering grades, were proved to be useful in this field. In detail, the multifarious roles played by the paper are discussed, highlighting how the paper can be a suitable material for electrochemical sensing while being capable of simplifying the measurement of complex real matrices or realizing programmable origami-like structures. Among the most important pollutants, a special focus is dedicated to the emerging pollutants. Furthermore, the unique advantages achieved by the paper have been analyzed and highlighted, reporting the future perspectives regarding the use of this surprising material. Graphical abstract: Image 1